Pengembangan Model Kebijakan Energi Terbarukan Berbasis Hutan Tanaman Rakyat Untuk Industri Biomasa yang Berkelanjutan - Erwin Susanto Sadirsan; Hermanto Siregar; Eriyatno Eriyatno; Evita H Legowo (STI Policy and Management Journal, 2014)
Renewable energy development strengthened due to considering Energy Act number 30 year 2007 article 21. Presidential Decree No. 5, 2006, mandate the target energy mix by 2025 to be 17% for new and renewable energy. Companies can contribute in terms of investment as Corporate Social Responsibility for Community Development interests. This study aimed to (1) formulate the development of renewable energy policy models, in particular biomass for rural electrification, (2) formulate the factors that influence the price of feed in tariff policy, in particular wood based biomass, (3) design the role of social forestry for raw materials biopelet industry in a sustainable supply chain. Research methods used techniques of Soft Systems Methodology, in the form of case studies supported by the literature to provide an alternative approach to solve the problems faced by leaders in the Indonesian Mining Company.